Ozone: A Multifaceted Molecule with Unexpected Therapeutic Activity - Zanardi, I.; Borrelli, E.; Valacchi, G.; Travagli, V.; Bocci, V. (Current Medicinal Chemistry, 2016)
A comprehensive outline for understanding and recommending the therapeutic use of ozone in combination with established therapy in diseases characterized by a chronic oxidative stress is currently available. The view of the absolute ozone toxicity is incorrect, because it has been based either on lung or on studies performed in artificial environments that do not correspond to the real antioxidant capacity of body compartments. In fact, ozone exerts either a potent toxic activity or it can stimulate biological responses of vital importance, analogously to gases with prospective therapeutic value such as NO, CO, H2S, H2, as well as O2 itself. Such a crucial difference has increasingly become evident during the last decade. The purpose of this review is to explain the aspects still poorly understood, highlighting the divergent activity of ozone on the various biological districts. It will be clarified that such a dual effect does not depend only upon the final gas concentration, but also on the particular biological system where ozone acts. The real significance of ozone as adjuvant therapeutic treatment concerns severe chronic pathologies among which are cardiovascular diseases, chronic obstructive pulmonary diseases, multiple sclerosis, and the dry form of age-related macular degeneration. It is time for a full insertion of ozone therapy within pharmaceutical sciences, responding to all the requirements of quality, efficacy and safety, rather than as either an alternative or an esoteric approach.
Keywords: Oxidative stress